Histoenzymic localation of phosphatases, oxidoreductases and esterases in the cervix of buffalo during fetal life* - UPPAL, VARINDER; ROY, K S; BANSAL, NEELAM (The Indian Journal of Animal Sciences, 2011)
The histoenzylnic localization of different enzymes was studied in cervices of 12 buffalo foetii collected from abattoir. The cryostat sections of 10-20 flm were subjected to different substrates for demonstration of enzymes. The study revealed a lnoderate to strong localization of most of the enzymes in lamina epithelialis and tunic muscularis whereas the propria submucosa and serosa showed a weak activity. Acetyl cholinesterase activity was localized in the neuronal elements. Â